2022
DOI: 10.1590/0004-282x-anp-2021-0192
|View full text |Cite
|
Sign up to set email alerts
|

A study on the correlation between pain frequency and severity and vitamin B12 levels in episodic and chronic migraine

Abstract: Background It is believed that vitamin B12 deficiency and hyperhomocysteinemia cause endothelial cell damage by increasing the levels of free oxygen radicals, which may, in turn, be related to the onset of migraine episodes. Objective The objective of our study was to ascertain a correlation between vitamin B12 levels and migraine attack frequency and pain severity. Methods 127 patients with migraine and 45 healthy controls who presented to Okmeydanı Training and Research Hospital were included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Vitamin B12 deficiency in association with hyperhomocysteinemia causes damage to endothelial cells, increasing free radical levels, which may be related to migraine episode generation [192]. Recent studies suggested that a vitamin B12 deficiency in chronic migraine can be induced by the frequent use of analgesics, which may alter vitamin B12 absorption [193]. Thanks to the positive modulation of the gut microbiota by physical exercise, the latter, especially the aerobic type, seems able to prevent the onset of chronic migraine, rather than being able to reduce the symptoms of chronic headaches already existing.…”
Section: Other Vitamin Supplementationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin B12 deficiency in association with hyperhomocysteinemia causes damage to endothelial cells, increasing free radical levels, which may be related to migraine episode generation [192]. Recent studies suggested that a vitamin B12 deficiency in chronic migraine can be induced by the frequent use of analgesics, which may alter vitamin B12 absorption [193]. Thanks to the positive modulation of the gut microbiota by physical exercise, the latter, especially the aerobic type, seems able to prevent the onset of chronic migraine, rather than being able to reduce the symptoms of chronic headaches already existing.…”
Section: Other Vitamin Supplementationsmentioning
confidence: 99%
“…Vitamin B12 deficiency in association with hyperhomocysteinemia causes damage to endothelial cells, increasing free radical levels, which may be related to migraine episode generation [192]. Recent studies suggested that a vitamin B12 deficiency in chronic migraine can be induced by the frequent use of analgesics, which may alter vitamin B12 absorption [193].…”
Section: Other Vitamin Supplementationsmentioning
confidence: 99%
“…The diagnostic criteria in this classification do not include the evaluation of the severity and frequency of painful attacks, which should be evaluated and specified [107,108].…”
Section: Introductionmentioning
confidence: 99%